Forestry Green Sukuk Model: Harmonizing Hifz al-Bi'ah for Sustainable Restoration in Indonesia - Rizky Wibowo; Furqon Khoiruddin; Nahar Surur; Akhmad Roja Badrus Zaman; Muhammad Mu’tamid Ihsanillah (Journal of Islamic Economic Laws, 2026)
The increasing intensity of hydrometeorological disasters in Indonesia, such as flash floods and landslides, is directly proportional to the rate of national forest degradation. Mitigation efforts through forest restoration face a structural barrier: a funding gap that cannot be fully covered by the state budget. Although Indonesia has issued Green Sukuk, its allocation remains concentrated in the energy and transportation infrastructure sectors, while the high-risk forestry sector remains neglected. This study aims to construct a Forestry Green Sukuk model that harmonizes the principle of environmental preservation (Hifz al-Bi'ah) with modern Islamic financial engineering. The research method employed is normative legal research using a conceptual and statutory approach to analyze the DSN-MUI Fatwa, OJK regulations, and the Presidential Regulation on Carbon Economic Value. The research findings indicate that the use of the Ijarah Maushufah fi Zimmah (IMfZ) contract for the leasing of future asset benefits is the most appropriate structure to mitigate biological risks and uncertainty (gharar) in forestry projects. Unlike profit-sharing schemes, the IMfZ model provides cash flow certainty by monetizing ecosystem services, specifically carbon sequestration and flood mitigation, as valid underlying assets. This study offers a theoretical contribution to the paradigm shift in Hifz al-Bi'ah and provides practical solutions for regulators to develop bankable alternative financing schemes that support climate resilience and disaster risk reduction targets in Indonesia.